Clay mineral analysis of the Vaca Muerta-Quintuco shale system northern Neuquén Basin, Argentina - Capelli, Ignacio Andrés (2017)
Neuquén basin represents the most productive gas basin in Argentina, while the VacaMuerta-Quintuco system(Tithonian-Valanginian) is considered as one of the most important unconventional plays in the world. In order toincrease productivity and predict their rheological behavior, detailed mineralogical analysis is essential on theseplays. This contributionallowed us to make a detailed characterization of the transition from a carbonate ramp(VacaMuerta Fm) to a mixed siliciclastic-carbonate shelf (Quintuco Fm). The analysis of clay minerals revealeda high-ordered illitic material dominated shale, with variable contribution of Fe-rich chlorite. The smectite-illiteinterlayers (I/S) of marlstones revealed a high ordering (R3), while the I/S of other lithologies showed a subtleincrease in expandibility, suggesting a different diagenetic process.In the outcrops of PuertaCuraco (NorthernNeuquén Province), the VacaMuerta Fm is ~400 m thick and consists ofrhythmic alternations of marlstones and limestones, with interbedded0.5-50 cm thick volcaniclastic layers (tuffs).Overlaying VacaMuerta Fm, Quintuco Fm (~300 m) consists of limestones, shales and fine-grainedsandstones,indicating a shallowing upward sedimentary cycle. The amount of clay minerals increases upward along the entiresystem while the carbonate content (calcite and dolomite) decreases (Kietzmannet al., 2016).Systematic sampling and mineralogical analysis (XRD) were performed on the entire sequence (~700 m) in orderto study the paleoenvironmental transition through the carbonate ramp to the mixed siliciclastic-carbonate shelf,and also to increase the knowledge about the diagenetic process.Considering the marlstones:limestones ratio, five composite third-order sequences were recognized, each onesubdivided into a transgressive system track and a regressive system track. No relation was observed betweensequence stratigraphy and clay mineralogy, except for the regressive system track of Quintuco Fm, that is characterizedby an important increase in clay mineral content, specially illite/mica.Marlstones represent the main lithology in the VacaMuerta Fm and XRD analysis revealed that clay mineralogyis dominated by illitic material, with subordinated rich Fe-chlorite. Illitic material is characterized by very littleamount ofexpandable layers. Limestones also present Fe-rich chlorite and illitic material with a subtle increase inexpandable layers. Tuffs may show either alteration to argillaceous minerals (80%) or replacement by carbonatematerial (20%) (calcite and dolomite), the clay fraction revealed an important amount of Fe-rich chlorite and alsointerstratified illite/smectite (I/S), and, when compared to marlstones, the I/S of the tuffs presents an increase inthe amount of expandable layers. The high amount of Fe-rich chlorite on tuffs deposits is expected considering thehigh amount of Fe-rich minerals in tuffs sediments. On the other hand, Quintuco Formation shales are characterizedby illite/mica, chlorite and small amounts of I/S. The great abundance of illite/mica evidences the progressiveshallowing upward system, reflecting an important increase of detrital input.Illitic material represents the main clay mineral in VacaMuerta Fm. This fact may support the idea proposed byWilson et al. (2016) who mentioned that I/S (R3) may, under particular conditions, crystallize from pore waters.The high-ordered I/S is consistent with other indicators such as pyrolysis analysis, that revealed Tmax~520ºC,characterizing this system as an overmature formation in PuertaCuraco. The difference observed on expandablelayers in tuffs (carbonated or argillaceous replaced)suggestsdifferent initial material for marlstones and for tuffs,conditioning the formation of different clay mineral associations during diagenesis.Preliminary interpretations indicate that clay minerals in VacaMuerta Fm mainly respond to diagenesis processes,while Quintuco Fm clay mineralogy may be dominated by detrital input. Finally, the advanced stage of theillitization process observed in PuertaCuraco section, is compatible with other indicators like pyrolysis analysis,characterizing the system in this part of the basin as an overmature formation.